Quality of life and psychological impact among chronic disease patients during the COVID-19 pandemic - Mohammed Al Maqbali; Ahmad Alsayed; Ibrahim Bashayreh (Wolters Kluwer Medknow Publications, 2022)
Objective: Patients diagnosed with chronic disease may experience psychological symptoms including depression, anxiety, insomnia, and fatigue, all of which may adversely affect their quality of life (QoL). The main objective of this study is to identify the level of QoL, to know the prevalence of these symptoms among chronic disease patients in Oman during the third wave of coronavirus disease 2019 (COVID-19) pandemic, and to explore the contributing factors. Methods: A cross-sectional and descriptive correlational design was used. Convenience sampling was used to recruit participants. Data were collected using the Functional Assessment of Chronic Therapy (FACT)-General, Hospital Anxiety and Depression Scale, the Insomnia Severity Index, and the FACT-Fatigue subscale via Qualtrics® software. Linear regression analyses were used to explore factors that were associated with QoL. Results: Of 990 patients with chronic disease who participated, the mean total QoL score was 67.7 (standard deviation = 16.1). Participants aged above 51, those with a basic education, those with heart disease, or those with more than one comorbidity had a significantly lower QoL. Linear regression revealed that the main factors associated with lower QoL included heart disease (β = 0.05, P = 0.02), diabetes (β = 0.12, P < 0.01), having taken one dose of COVID-19 vaccine (β = 0.05, P = 0.04), anxiety (β = −0.24, P < 0.01), depression (β = −0.31, P < 0.01), insomnia (β = −0.12, P < 0.01), and fatigue (β = 0.27, P < 0.01). Conclusions: The COVID-19 pandemic has significantly reduced the individuals' level of QoL and affected the mental health of patients diagnosed with chronic diseases. Appropriate strategies to monitor psychological problems and interventions to prevent and reduce these among such patients are needed.